Physiological response of locusts to eye stimulation by spectral illumination for phototactic pest control - Qihang, Liu; Qiang, Zhou (International Journal of Agricultural and Biological Engineering, 2016)
To provide theoretical support for study of locust phototactic vision nature, the locust phototactic physiology and visual spectrum effects were investigated by stimulating the visual system using light from an AvaSpec fiber-optic spectrometer and Flir thermal imaging system. When light stimulated the locust visual system, the biological photoelectric transformation effect of the visual system caused by photon energy, presented with the higher physiological temperature on the forehead, as tested by the Flir thermal system. After stimulation with light, the different absorption degrees of the vision system on the spectral photons, as tested by the AvaSpec spectrometer, showed that the phototactic response to light had the simultaneous requirements of lighting intensity and time. The absorbing differences of spectral photons by the vision system demonstrated the absorption selectivity under light stimulation, as exhibited by the sensitive absorption of spectral energy at 430 nm, 545 nm and 615 nm. Moreover, the higher forehead temperature increment indicated and induced the stronger physiology activity which was the reason that causing the good phototactic response degree of locusts with 30 min light stimulation, and the adaption time was about 60 min. Therefore, only when the visual reaction effect was stimulated to absorb sensitive spectral energy and generate the physiological exciting response could cause the phototactic behavior. Keywords: Phototactic pest control, physiological response, Locusta migratoria, spectral illumination, phototactic vision, spectrum absorption, light simulation DOI: 10.3965/j.ijabe.20160902.1249 Citation: Liu Q H, Zhou Q. Physiological response of locusts to eye stimulation by spectral illumination for phototactic pest control. Int J Agric & Biol Eng, 2016; 9(2): 186－194.